PENINGKATAN KETAHANAN BAWANG MERAH TERHADAP PENYAKIT LAYU FUSARIUM MELALUI INDUKSI KETAHANAN DENGAN ASAM SALISILAT SECARA INVITRO - Muhammad Juwanda; Khusnul Khotimah; Mohamad Amin (Agrin, 2016)
Fusarium whitere disesase or moler is a major disesase on shallot that is caused by Fusarium oxypsporumf. Sp. Cepae (Foc), it is spread soil mushroom kind and generally sistemacally hence it’s dificult controled byfungicid. Suffer caused by this moler disesase can reache 50% moreover can cause failed fiver. For that reasonit needs the use of varietes endurance of moler disesase and high productivity. Endurance induction is one of themethods to get shallot cultivar endure fusarium whietere disease. Endurance induction can be done in vitro withthe inducing agent is chemist matter likes salisilic acid. For knowing the respon of salisilyc acid in inducing theindurance is done by using fusarat acid as selector matter to get endurance planlet. This research is done torecogize the respon of bud Bima cultivar shallot of Brebes in vitro againts the effectity of salisilyc acid of vareitesof concentration (0 ppm, 2.5 ppm, and 7.5 ppm) in inducing endurance then it’s done selection to get endurancecharacter of disease by exogen salisilyc acid able to impove shallot planlet endurance that is showen by descentintensities of fusarium attact, descending planlet endurance status form susceptibe become moderate. The bestconcentration of salisilyc acid in inducing onion planlet endurance is 5 ppm and 7.5 ppm.Key words: induction of endurance, salsilyc acid, fusarat acid, shallot.